From structure to ætiology: a new window on the biology of leucine-rich repeat kinase 2 and Parkinson's disease. Issue 14 (30th July 2021) - Herbst, Susanne; Lewis, Patrick A.
Abstract : Since the discovery of mutations in leucine-rich repeat kinase 2 (LRRK2) as an underlying genetic cause for the development of Parkinson's disease (PD) in 2004 (Neuron 44, 601–607; Neuron 44, 595–600), and subsequent efforts to develop LRRK2 kinase inhibitors as a therapy for Parkinson's (Expert Opin. Ther. Targets 21, 751–753), elucidating the atomic resolution structure of LRRK2 has been a major goal of research into this protein. At over 250 kDa, the large size and complicated domain organisation of LRRK2 has made this a highly challenging target for structural biologists, however, a number of recent studies using both in vitro and in situ approaches (Nature 588, 344–349; Cell 182, 1508–1518.e1516; Cell 184, 3519–3527.e3510) have provided important new insights into LRRK2 structure and the complexes formed by this protein.